Diffuse Erythematous Follicular Eruption Induced by Pegylated Liposomal Doxorubicin - Zhong L; Hu J; Hu Y; Chen X; Jin J; Li H (Clinical, Cosmetic and Investigational Dermatology)
Lingzhi Zhong,* Jian Hu,* Yuqing Hu, Xue Chen, Jiang Jin, Houmin Li Department of Dermatology, Peking University People’s Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Houmin Li, Email lhoumin@sina.cnAbstract: Pegylated liposomal doxorubicin (PLD) is a form of doxorubicin enclosed in pegylated liposomes and is associated with a high risk of mucocutaneous side effects. The most common cutaneous side effect is hand-foot syndrome, whereas other cutaneous reactions are rarely reported. The pathogenesis of PLD-induced cutaneous reaction is not yet clear. It is presumed that PLD could discharge through sweat or damaged vessels and impair keratinocytes in the basal layer or hair follicles as well as induce lymphocytic inflammation. We report a relatively rare of PLD-induced cutaneous reaction presented as diffuse follicular rashes and intertrigo-like dermatitis. A 56-year-old man, with leiomyosarcoma, developed pruritic and painful follicular erythematous papules with scaling on the trunk and limbs after receiving three cycles of PLD. The patient discontinued the use of PLD because of pain and exacerbation of the eruptions, and then the rashes gradually disappeared. This case highlights the potential pathogenesis underlying this unusual cutaneous reaction related to Pegylated Liposomal Doxorubicin.Keywords: pegylated liposomal doxorubicin, diffuse follicular rash, intertrigo-like dermatitis